Operation type and phase specific compliance with WHO surgical safety guidelines checklist at the mother and child hospital - Agus Budi Prasetyo; Ircham Saifudin; Widigdo Rekso Negoro; Muhammad Rodli; Sindu Sintara; Annes Rindy Permana (International Journal of Public Health Science (IJPHS), 2026)
The surgical safety checklist (SSC) is a recognized tool for enhancing patient safety by reducing surgical complications and mortality. While its benefits are well established, effective implementation depends on consistent adherence by the medical team. This study examined the relationship between surgical procedure type and team compliance with SSC in the central operating room of a maternal and child hospital in Yogyakarta. Using a quantitative cross-sectional design, data were collected from 65 observed operations out of 148 total procedures, including elective and emergency cases. Compliance was evaluated in three SSC phases: sign-in, time-out, and sign-out. Correlation was analyzed using chi-square tests. The results showed no significant relationship in the sign-in phase (p = 0.195), but significant correlations were found in the time-out (p = 0.004) and sign-out (p = 0.011) phases. Overall, a significant association was identified between type of surgery and SSC compliance (p = 0.006). This study concludes that SSC compliance remains suboptimal, particularly in the initial phase. Elective procedures demonstrated higher compliance than emergency cases. Strengthening a culture of safety and promoting interdisciplinary training are essential strategies to improve SSC adherence and elevate surgical care quality.